1998
DOI: 10.1038/sj.onc.1201908
|View full text |Cite
|
Sign up to set email alerts
|

Exon III splicing switch of fibroblast growth factor (FGF) receptor-2 and -3 can be induced by FGF-1 or FGF-2

Abstract: An essential feature of ®broblast growth factor receptors (FGFRs) is the existence of multiple possibilities of alternative splicing. One of these concerns sequences of the mRNA coding for the C-terminal half of Ig domain 3 which corresponds to a part of the ligand-binding site: two alternative exons, IIIb and IIIc, encode the Cterminal half of Ig domain 3. The IIIb/IIIc choice in the FGFR-2 and FGFR-3 is strictly tissue-speci®c, the IIIb exon being expressed exclusively in epithelial cells. We describe here a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
0
16
0
2
Order By: Relevance
“…Expression of FGFR3 IIIb appears to be associated with epithelial cells [20,32]. A switch from IIIb to IIIc can be induced by FGF1, possibly correlating with a loss of epithelial phenotype [33]. In contrast, cytokines or growth factors such EGF, TGFh and IL2, have been shown to upregulate FGFR3 IIIb expression in the intestinal epithelial cell line Caco2 [34].…”
Section: Expression Of Fgfr3 In Tissues and Its Biological Rolesmentioning
confidence: 98%
“…Expression of FGFR3 IIIb appears to be associated with epithelial cells [20,32]. A switch from IIIb to IIIc can be induced by FGF1, possibly correlating with a loss of epithelial phenotype [33]. In contrast, cytokines or growth factors such EGF, TGFh and IL2, have been shown to upregulate FGFR3 IIIb expression in the intestinal epithelial cell line Caco2 [34].…”
Section: Expression Of Fgfr3 In Tissues and Its Biological Rolesmentioning
confidence: 98%
“…In human keratinocyte SVK14 cells, the splicing switch of FGFR-2 was induced by FGF-2. 37 A similar mechanism of alternative splicing of the human NPM gene should occur upon expression of the nuclear 24 kDa FGF-2 in HeLa cells. This control could be mediated by the induction of particular splicing factors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, FGFR2c was reported to bind FGF1 and FGF2 with equal affinity, whereas FGFR2b bound FGF2 with a thousand-fold lower affinity than FGF1 (11). It has also been suggested that the expression of b and c FGFR isoforms can be "reversibly switched" by the influence of FGF1 or FGF2 (12). Aberrant receptor switching has been reported to be involved in the progression of certain tumors (13).…”
mentioning
confidence: 99%